STUDIES ON THE CARYOLOGY OF SOME SPECIES OF THE GENUS SUAEDA (CHENOPODIACEAE) IN IRAN (Journal of Sciences, Islamic Republic of Iran)
Caryological studies were carried out on ten species of the genus Suaeda belonging to 27 samples of different populations in Iran. Important chromosome features including numbers, lengths, centromere locations and caryotypes were studied. All the species have basic chromosome numbers of x=9. Chromosome counts of S. acuminata (C.A.Mey.) Moq. (2n=18), S. aegyptiaca (Hasselq.) Zoh., (2n=l8), S. baluchistanica Akhani and Podl. (2n=72), S. crassifolia Pall., (2n = 18), and S. microsperma (C.A.Mey.) Fenzel, (2n=18) are given for the first time. Another chromosome number for S. fruticosa J.F.Gmelin (2n=72) is also reported